The Restoration of Paintings at the Imperial Hermitage (Saint-Petersburg) at the Beginning of the 19th Century - Mariam Nikogosyan (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The beginning of the 19th century was a period of formation of restoration school in Russia. F.K.Labensky, Curator of the Hermitage Picture Gallery from 1797 onwards till 1850, arranged a restoration studio with a permanent staff working on Imperial painting collection.  Labensky’s assistant, a restorer A.F. Mitrokhin learned all known techniques of mechanical restoration – relining, cradling and even transfer of paintings, - and developed them on his own. A special school was established by the Hermitage studio in 1819, supervised by Mitrokhin, were young graduates of Imperial Academy of Art were taught both mechanical and painting restoration. The apprentices of Mitrokhin school passed his techniques to next generation of Hermitage restorers.